Genomic characterization of Pantoea dispersa A003 isolated from a clinical patient - Wang, Licheng; Wang, Xiaoxia; Chen, Shaojin; Zhong, Shan; Xu, Lixia; Zhu, Xiong; Dong, Lingzhi (Frontiers in Bacteriology, 2024)
Introduction Pantoea dispersa is a Gram-negative bacterium generally considered as a plant pathogen and rarely causes human infections. To date, there have been 13 studies that have documented clinical infections linked to P. dispersa, with a primary emphasis on the initial identification of this pathogen. The genomic features and the mechanisms underlying the pathogenesis of P. dispersa remain largely uninvestigated. In the present study, we describe a clinical infection caused by P. dispersa and provide the first genomic analysis of this bacterium. Methods The bacterial strain designated A003 was isolated from blood samples. Preliminary identification of strain A003 was conducted using matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) technology (VITEK® MS, bioMérieux, France). Biochemical and antimicrobial susceptibility assessments were carried out utilizing the VITEK-2 compact automated microbial analysis system (bioMérieux, France). Additionally, whole genome sequencing and subsequent analysis were performed to further elucidate the potential pathogenicity. Results The bacterial isolate was cultured overnight at 35°C in a CO2-enriched environment on Columbia blood agar, resulting in the appearance of a white, smooth, Gram-negative rod-shaped bacterium with diameters ranging from 1 to 2 mm. Identification of strain A003 was achieved with a high confidence level of 99.9% as P. dispersa using MALDI-TOF mass spectrometry. The average nucleotide identity (ANI) value between strain A003 and the reference strain P. dispersa DSM 30073T was 98.08%, while the DNA–DNA hybridization (DDH) value was 84.10% (Formula 2) based on genome sequencing data, which further confirmed that A003 belonged to the P. dispersa species. Comprehensive analysis revealed the presence of 372 virulence factors, 15 antibiotic resistance genes, 222 carbohydrate-active enzymes, and 666 genes related to Type III secretion system (T3SS) effector proteins, as identified through the core databases of VFDB (Virulence Factors of Pathogenic Bacteria), CARD (Comprehensive Antibiotic Resistance Database), CAZY (Carbohydrate-Active enZYmes Database), and T3SS. The virulence factors included type IV pili (TFP), type VI secretion system, flagella, iron uptake system, and ompA, which are implicated in bacterial pathogenicity. The antibiotic resistance profile indicated resistance to fluoroquinolones, cephalosporins, penams, macrolides, and aminoglycosides, as annotated by the CARD database. Conclusion The draft genome sequenced represents the inaugural genomic sequence of P. dispersa derived from clinical sources. This advancement may enhance clinical practitioners’ comprehension of the organism’s clinical attributes and serve as a foundational resource for future research into its virulence, antibiotic resistance, and host–pathogen interactions.